PELATIHAN APLIKASI PENCATATAN KEUANGAN BAGI RUMAH TANGGA DAN UMKM DI DESA PERMANU - Sugiastuti, Reika Happy; Nur Imamah; Ika Ruhana; Anni Rahimah (Wisesa: Jurnal Pengabdian Masyarakat, 2024)
Community service is one of the Tridharma activities of higher education in addition to the dharma of education and research. The methods used in this activity include analyzing community conditions, identifying problems, determining specific work goals, problem solving plans, social approaches, carrying out outreach and training activities, and evaluating results. Before implementation, the research team analyzed and identified problems in the community in Permanu Village. The results of the analysis show that the Permanu Village community is still weak in financial management, and it is identified that this occurs because they do not record their finances properly, especially households and MSMEs. Next, provide counseling on financial management and continue with direct training on financial recording with applications. The results of the service showed that the training succeeded in increasing participants' understanding and skills in using digital financial recording applications, and many were interested in continuing to learn about financial management. This training can have a long-term positive impact on the financial management of households and MSMEs in Permanu Village, as well as increasing their access to financial facilities such as bank credit.